ВИНКАНИН ВА ПИРАЗОЛИН ИНДОЛ АЛКАЛОИДЛАРИНИНГ КАРДИОПРОТЕКТОР ТАЪСИРИДА КАТФ-КАНАЛЛАРИНИНГ РОЛИ - Жумаев, И.З.; Бобоев, С.Н.; Есимбетов, А.Т. (SCIENCE and SOCIETY, 2024)
The article studied the effect of indole alkaloids vincanine and pyrazoline on the contraction activity of the papillary muscles of the heart of rats under hypoxic conditions. The indole alkaloids vincanine and pyrazoline have been found to have potent cardioprotective properties. It is described that the cardioprotective properties of these alkaloids are provided by modulating KATP -channels in the membrane of cardiac muscle cells.